Edukasi Milenial Melek Finansial Akuntansi Manajemen Berorientasi Pelanggan - Norsita, Mega (Jurnal Abdi Masyarakat Nusantara, 2023)
Abstract: One of the successes of a business is largely determined by how to build communication with customers. Customers are very important business partners for companies because this is where the company's products, processes and services interact to generate profits. This activity is to illustrate how understanding and implementing customer-oriented management accounting is very important in building appropriate and effective communication concepts in identifying, maintaining customer needs and desires. Management accounting itself is an important part of managing the business being run, both in the process of planning, monitoring and evaluating sales performance. Through education that correlates knowledge between management and consumer orientation in shopping, business management can be improved in the business being run. Keyword: Millenia; Customer Orientation; Management Accounting.